THE INFLUENCE OF LEADERSHIP STYLE, WORK DISCIPLINE, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. KELOLA KARYA BERSAMA - Saputri, Dian; Adrian, Adrian; Frederick, Henry Waidan (Jurnal Manajemen & Bisnis Jayakarta, 2022)
This study aims to analyze Leadership Style, Work Discipline, and Work on Employee Performance at PT. Kelola Karya Bersama. The variables studied are Leadership Style, Work Discipline, Job Satisfaction, and Employee Performance. The type of research used is a quantitative research type, and the kind of data is primary data through the questionnaire method with the sampling technique used is purposive sampling with the number of respondents forty-six (46) respondents. Data analysis in this study used SPSS version 26.0. The analysis used in this research is the Validity Test, Reliability Test, Multicollinearity Test, Heteroscedasticity Test, Normality Test, Multiple Linear Analysis, Correlation Coefficient Analysis Test, T-test, F-test, and Coefficient of determination (R2). The results of testing and analysis of this research show that leadership style, work discipline, and satisfaction work simultaneously or together significantly affect employee performance. Suggestions for Kelola Karya Bersama in the future are to improve an excellent and fair leadership style further and enforce employee discipline in doing work to create employee satisfaction and increase company productivity.